Development and characterization of oil palm empty fruit bunch fibre reinforced polylactic acid filaments for fused deposition modelling / Vignesh Sekar, Mazin Zarrouq and Satesh Narayana Namasivayam - Sekar, Vignesh; Zarrouq, Mazin; Namasivayam, Satesh Narayana (Universiti Teknologi MARA, 2021)
In recent years, Natural Fibre-Reinforced Composites (NFRC) making its impact in all applications, and they have reached their way into the field of Additive Manufacturing (AM) as well. This increases the demand for natural fibre based filaments in the field of AM. Hence, this research aims to develop filaments made of Polylactic acid (PLA) reinforced with Oil Palm Empty Fruit Bunch Fibre (OPEFBF) and to investigate its physical, thermal and mechanical properties. PLA with 10, 20, 30, and 40 wt.% of OPEFBF were melt blended, hot-pressed, and successfully extruded as filaments. Later, its physical, thermal, water absorption, biodegradation, and mechanical properties are investigated. OPEFBF reinforced filaments show lesser values of densities, increased Tensile Modulus (TM), better bio and thermal degradation compared to the pure PLA. However, its rate of water absorption is high with reduced Tensile Strength (TS) than the pure PLA. Later these filaments reinforced with different OPEFBF contents are 3D printed using Fused Deposition Modeling (FDM) technology. Filaments with lesser fibre content were easy to print. Filaments with 10 wt.% OPEFBF was continuously printed whereas, filaments with higher fibre content clogged in the nozzle. Overall, PLA reinforced with OPEFBF has been developed and successfully applied to the field of additive manufacturing by FDM.